Transitioning a bachelor of science in nursing program to blended learning: Successes, challenges & outcomes. - Posey, Laurie; Pintz, Christine (Nurse Education in Practice, 2017)
To help address the challenges of providing undergraduate nursing education in an accelerated time frame, the Teaching and Transforming through Technology (T3) project was funded to transition a second-degree ABSN program to a blended learning format. The project has explored the use of blended learning to: enable flexible solutions to support teaching goals and address course challenges; provide students with new types of independent learning activities outside of the traditional classroom; increase opportunities for active learning in the classroom; and improve students' digital literacy and lifelong learning skills. Program evaluation included quality reviews of the redesigned courses, surveys of student perceptions, pre- and post-program assessment of students' digital literacy and interviews with faculty about their experiences with the new teaching methods. Adopting an established quality framework to guide course design and evaluation for quality contributed to the efficient and effective development of a high-quality undergraduate blended nursing program. Program outcomes and lessons learned are presented to inform future teaching innovation and research related to blended learning in undergraduate nursing education.